Criminal Sanctions Against Narcotics Abuse for Himself Associated with Article 127 Law Number 35 of 2009 Concerning Narcotics - Anthoni Hutabarat; Rr. Dijan Widijowati (Global Writing Academica Researching & Publishing, 2023)
The purpose of this research is to analyze Criminal Sanctions Against Narcotics Abuse for Himself Associated with Article 127 Law Number 35 of 2009 Concerning Narcotics. The type of research used in this study is a type of normative legal research, namely viewing and analyzing from the point of view of laws and regulations that apply, especially those related to the problems in this study. The results of the research that the mistake of imposing prison sentences on narcotics abusers occurred since the enactment of Law Number 22 of 1997 concerning Narcotics until now has not changed, even though the Narcotics Law changed to Law Number 35 of 2009 concerning narcotics, explicitly stating the purpose of making the law is